PERAN Peran Guru Penggerak dalam Implementasi Kebijakan Merdeka Belajar - Muhammad Faiq Hirzulloh (Institut Agama Islam Sunan Giri Ponorogo, 2024)
The purpose of this study is to find out how the implementation of learning independence learning through the role of the driving teacher. Qualitative research methodology was used in this study. This type of research is classified as library research. The technique used for data analysis in this study is content analysis. The descriptive presentation of the research findings is based on the research problem and objectives. The findings of this study reveal the strategic role of motivating teachers, including: (1) functioning as motivators in schools based on their teaching experience, thus involving all components of education in an effort to improve the quality of education; (2) motivating teachers in fostering learner independence by guiding and shaping learners in their holistic development; (3) transformative changes in education patterns facilitated by motivating teachers, moving from centralized approaches to decentralized institutions, with teachers and schools as leaders of the transformation process; (4) motivating teachers as leaders in learner independence, able to drive the education ecosystem towards learner-centered education.